Liver HLA-E Expression Is Associated with Severity of Liver Disease in Chronic Hepatitis C - Roberta C. Araújo; Fabricio C. Dias; Bruna C. Bertol; Deisy M. Silva; Patrícia H. Almeida; Andreza C. Teixeira; Fernanda F. Souza; Marcia G. Villanova; Leandra N. Z. Ramalho; Eduardo A. Donadi; Ana L. C. Martinelli (Journal of Immunology Research)
Hepatitis C virus (HCV) can escape from innate and adaptive immunity, making the immune response ineffective. Human leukocyte antigen E (HLA-E) might regulate the antiviral function of immune response and contribute to the persistence of HCV and the severity of liver disease. This study aimed to evaluate the expression of HLA-E in the liver and its association with the severity of liver disease in HCV patients. We performed a retrospective analysis of liver biopsies from 125 HCV patients and from 20 control subjects without liver disease. Liver biopsies were reviewed and classified according to severity of fibrosis and inflammatory activity. The pathologist assessed the magnitude of HLA-E expression in a semiquantitative way, attributing scores from 0 to 3. Immunohistochemistry showed positive for HLA-E in hepatocyte and Kupffer cells. The rate of HLA-E positivity in hepatocytes and Kupffer cells was significantly higher in HCV patients compared to controls. The liver samples classified as severe fibrosis and necroinflammatory activity presented greater expression of HLA-E on Kupffer cells and hepatocytes, with a significant linear association. It indicates that HLA-E expression may have an immunomodulatory effect and a possible role in the severity of liver disease in chronic hepatitis C.